Levels of trimethylamine N-oxide and lipopolysaccharides in vascular and idiopathic erectile dysfunction - Özdeş, Ahmet Alper; Kaymaz, Tuğçe; Karakeçi, Ahmet; Gürsu, Mehmet Ferit; Osmanlıoğlu, Fatih (Cellular and Molecular Biology Association, 2025)
The gut microbiota influences endothelial dysfunction through metabolites like lipopolysaccharides (LPS) and trimethylamine-N-oxide (TMAO), affecting cardiovascular health and contributing to atherosclerosis and hypertension development. We evaluated TMAO and LPS levels in patients with vascular and idiopathic erectile dysfunction (ED). In this study of 151 participants (50 vascular ED, 50 idiopathic ED, 51 healthy controls), patients were categorized using comprehensive clinical assessment including International Index of Erectile Function (IIEF), laboratory tests, and imaging methods. While age (mean 55.15±7.17 years) and TMAO levels showed no significant differences between groups (p>0.05), LPS levels were significantly elevated in the vascular ED group (497.36±87.83) compared to idiopathic ED (430.62±69.72) and control groups (436.98±105.37) (p<0.05). These findings suggest that gut microbiota metabolites, particularly LPS, play a significant role in ED pathophysiology through endothelial dysfunction. Regulating gut microbiota may serve as both a protective factor against ED development and a potential treatment option for existing cases. Further comprehensive studies are warranted to explore these therapeutic possibilities. © 2025, Cellular and Molecular Biology Association. All rights reserved.
Keywords: Endothelial damage; Idiopathic erectile dysfunction; Lipopolysaccharide (LPS); Tri-methylamine N-oxide (TMAO); Vascular erectile dysfunction